2023
DOI: 10.1002/pbc.30556
|View full text |Cite
|
Sign up to set email alerts
|

Children's Oncology Group's 2023 blueprint for research: Soft tissue sarcomas

Abstract: In the United States, approximately 850–900 children and adolescents each year are diagnosed with soft tissue sarcomas (STS). STS are divided into rhabdomyosarcoma (RMS) and non‐rhabdomyosarcoma STS (NRSTS). RMS and NRSTS are risk stratified into low‐, intermediate‐, and high‐risk categories, with 5‐year survival rates of approximately 90%, 50%–70%, and 20%, respectively. Recent key achievements from the Children's Oncology Group (COG) STS Committee include the identification of new molecular prognostic factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 134 publications
0
2
0
Order By: Relevance
“…While rhabdomyosarcoma (RMS) cure rates exceed 70%, certain subsets of patients remain at higher risk of recurrence, including those with unfavorable histology, primary disease at unfavorable sites, and metastatic disease at diagnosis. 1,2 Relapsed and refractory RMS (RRMS), excluding patients with initially low-risk features, carries a dismal prognosis, with a 5-year overall survival (OS) from first recurrence of less than 20%. 3 Ongoing investigation of novel therapies and treatment strategies is essential to improve survival for RRMS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While rhabdomyosarcoma (RMS) cure rates exceed 70%, certain subsets of patients remain at higher risk of recurrence, including those with unfavorable histology, primary disease at unfavorable sites, and metastatic disease at diagnosis. 1,2 Relapsed and refractory RMS (RRMS), excluding patients with initially low-risk features, carries a dismal prognosis, with a 5-year overall survival (OS) from first recurrence of less than 20%. 3 Ongoing investigation of novel therapies and treatment strategies is essential to improve survival for RRMS.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 While the myelosuppressive toxicity seen with rebeccamycin analog halted its further development, vinorelbine has been further developed in multiple RMS COG studies: a relapsed combination trial (ARST0921), a randomized phase 3 intermediate-risk trial where it was incorporated into maintenance chemotherapy with oral cyclophosphamide (ARST1431), and an ongoing high-risk randomized phase III clinical trial (ARST2031). 2,9 The use of radiologic response as an activity endpoint in RRMS provides multiple limitations. First, several studies have shown conflicting findings between the relationship of an early radiographic response and long-term outcome in newly diagnosed RMS.…”
Section: Introductionmentioning
confidence: 99%